ANALISIS SOAL UJIAN AKHIR SEMESTER PADA MATA PELAJARAN IPA BERDASARKAN DIMENSI PROSES KOGNITIF TAKSONOMI ANDERSON DANKEMAMPUAN BERPIKIR KRITISDI SMP NEGERI 1 NUNUKAN SELATAN - Fitriani Fitriani; Ibrahim Ibrahim; Endik Deni Nugroho (Biopedagogia, 2020)
The final exam is a summative evaluation applied by schools to measure student’s cognitive learning outcomes which are usually given in the form of tests. The analysis of each test item is expected to be useful to make improvements and refinement of the items that have been tested on students. The type of research is a qualitative descriptive study. The sample in this study were all manuscripts of final exam questions for natural science subjects of VII, VIII, and IX grades Negeri 1 Nunukan Selatan on 2018 Academic Year. Data collection is done by means of documentation and interviews. Data were analyzed according to operational verbs in the dimensions of Anderson's Taxonomy cognitive process and aspects of critical thinking skills. The results showed that (1) the distribution of the cognitive process dimensions of Anderson's Taxonomy in the questions was not evenly distributed, the questions were dominated by the dimensions of cognitive processes at levels C1, C2 and C3. The percentage of cognitive dimensions in VII grade namely C1 gained 44%, C2 gained 44% and C3 gained 12%. The VIII grade namely C1 gained 20%, C2 gained 46.7%, C3 gained 26.7% and C4 gained 6.7%. The IX grade namely C1 gained 2.8%, C2 gained 25.7%, C3 gained 42.8%, and C4 gained 28.5%; (2) the distribution of critical thinking skills aspects in the questions is also not evenly distributed, the questions are dominated in aspects 1 and aspect 2. The percentage of critical thinking skills aspects in VII grade is A1 gained 44% and A2 gained 56%. The VIII grade is A1 gained 46.7%, A2 gained 43.3% and A3 gained 10%. The IX grade is A1 gained 5.7%, A2 gained 48.5%, A3 gained 40% and A5 gained 5.7%. Keywords:  Question, Cognitive, Anderson’s Taxonomy, Critical thinkingANALISIS SOAL UJIAN AKHIR SEMESTER PADA MATA PELAJARAN IPA BERDASARKAN DIMENSI PROSES KOGNITIF TAKSONOMI ANDERSON DANKEMAMPUAN BERPIKIR KRITISDI SMP NEGERI 1 NUNUKAN SELATAN